Antitumoral properties of two new vanadyl(IV) complexes in osteoblasts in culture: role of apoptosis and oxidative stress - Molinuevo, María Silvina (2004)
Background: Vanadium derivatives have been reported to display different biological effects, and in particular antineoplastic activity has been demonstrated in both in vivo and in vitro studies. Purpose: To study the effect of two new organic vanadyl(IV) complexes (one with glucose, GluVO, and the other with naproxen, NapVO) in osteosarcoma cells. Methods: UMR106 osteosarcoma cells and, for comparison, nontransformed MC3T3E1 osteoblasts were used. Proliferation and differentiation were assessed using the crystal violet assay and ALP specific activity, respectively. Morphological alterations were assessed by light microscopy. Lipid peroxidation was evaluated in terms of production of thiobarbituric acid-reactive substances (TBARS) and apoptosis was measured using annexin V. Extracellular regulated kinase (Erk) activation was investigated by Western blotting. Results: Vanadium complexes caused morphological alterations and they strongly inhibited UMR106 cell proliferation and differentiation. In contrast, in MC3T3E1 cells, these vanadium derivatives had a relatively weak action. In UMR106 tumoral cells there was a significant increase in TBARS production. Both vanadium complexes induced apoptosis and activation of Erk. PD98059, an inhibitor of Erk phosphorylation, did not block the vanadium-induced antitumoral action. However, the antioxidants vitamins C and E abrogated the apoptosis and TBARS production induced by the vanadium complexes. Conclusions: GluVO and NapVO exerted an antitumoral effect in UM106 osteosarcoma cells. They inhibited cell proliferation and differentiation. While the Erk cascade seems not to be directly related to the bioactivity of these vanadium derivatives, the action of both vanadium complexes with organic ligands may be mediated by apoptosis and oxidative stress.